Inhibition of TGF-β Signaling in Gliomas by the Flavonoid Diosmetin Isolated from Dracocephalum peregrinum L. - Yuli Yan; Xingyu Liu; Jie Gao; Yin Wu; Yuxin Li (Molecules, 2020)
Background: Dracocephalum peregrinum L., a traditional Kazakh medicine, has good expectorant, anti-cough, and to some degree, anti-asthmatic effects. Diosmetin (3′,5,7-trihydroxy-4′-methoxyflavone), a natural flavonoid found in traditional Chinese herbs, is the main flavonoid in D. peregrinum L. and has been used in various medicinal products because of its anticancer, antimicrobial, antioxidant, estrogenic, and anti-inflammatory effects. The present study aimed to investigate the effects of diosmetin on the proliferation, invasion, and migration of glioma cells, as well as the possible underlying mechanisms. Methods: 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT), scratch wound, and Transwell assays were used to demonstrate the effects of diosmetin in glioma. Protein levels of Bcl-2, Bax, cleaved caspase-3, transforming growth factor-β (TGF-β), E-cadherin, and phosphorylated and unphosphorylated smad2 and smad3 were determined by Western blots. U251 glioma cell development and progression were measured in vivo in a mouse model. Results: Diosmetin inhibited U251 cell proliferation, migration, and invasion in vitro, the TGF-β signaling pathway, and Bcl-2 expression. In contrast, there was a significant increase in E-cadherin, Bax, and cleaved caspase-3 expression. Furthermore, it effectively reduced the tumorigenicity of glioma cells and promoted apoptosis in vivo. Conclusion: The results of this study suggest that diosmetin suppresses the growth of glioma cells in vitro and in vivo, possibly by activating E-cadherin expression and inhibiting the TGF-β signaling pathway.